DIGITAL TRADE CONGREGATES WITH CULTURAL INTELLIGENCE: THE DYNAMICS OF CROSS BORDER E-COMMERCE (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Global e-commerce has evolved and has become a significant part of the international trade. E-commerce growth effects the entire world market. While technology and logistics have played an imperative role in enhancing global trade, one of the key differentiators that has emerged in businesses seeking their presence across the world has been cultural intelligence. The current study explores the intersection of digital trade with cultural awareness thus highlighting the strategic relevance of adapting diverse cultural nuances like language, values, behavioural patterns across the globe. The study delves deeper into success stories of global brands like Alibaba, Amazon and Netflix and showcases how businesses are capable of integrating cultural intelligence with their e-commerce strategies. The study also examines the challenges that arise out of cross-cultural misalignments thus leading to brand rejections and loss of reputation. As digital trade escalates around the globe, being culturally intelligent is definitely an added advantage for businesses that seek to grow..
Keywords: Digital Trade; Cultural Intelligence; Global Consumer Behaviour; Market Expansion; Cross-Border E-Commerce; Localization